Tumble Motion Evolution for GDI Engine using Particle Image Velocimetry (PIV) / Mohammed EL-Adawy ... [et al.] - EL-Adawy, Mohammed; Heikal, M.R.; A. Aziz, A. Rashid; Siddiqui, M. I; Abdul Wahhab, Hasanain A.; Hasanain A., Hasanain A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In internal combustion engines (ICE), the intake generated flows are known to have a fundamental influence on the combustion both in spark ignition (SI) and compression ignition (CI) engines. The present study illustrates an experimental study on the airflow inside the cylinder of a gasoline direct injection (GDI) engine under steady-state conditions using particle image velocimetry (PIV). PIV measurements were conducted through the central vertical tumble plane, passing through the middle of the cylinder. The results illustrate how the flow direction was transferred from reverse tumble motion at low valve lifts to normal tumble motion at high valve lifts with nondimensional rig tumble of -0.23 and 0.69 at valve lift 1 and 9 mm respectively.